The Effect of Plyometric Upper Body Exercises on Long-Range Throwing Ability in Football Games - Muh. Ikbal Hidayattuloh; Tedi Supriyadi; Aam Ali Rahman (Journal of Physical Education Health and Sport, 2026)
This study is motivated by a lack of attention to upper body strength training in football training programs, even though this strength plays an important role in improving  the ability to throw inside. Football training programs generally emphasize more on foot technique so that the development of the strength of the shoulder, arm, and upper body muscles has not been carried out optimally. This study aims to determine the effect of upper body plyometric exercise (UBPT) on the improvement of throwing ability inward in football players. The research method used is a quantitative approach with  a pre-experimental design using a pretest-posttest design of one group. The study participants amounted to 24 PS Ranc FC Football School players in the age group of 14 years who were selected through purposive sampling techniques. Data collection was carried out through throw-in tests at the pretest and posttest stages after the implementation of 12 UBBT training sessions. Data analysis used normality test, homogeneity test, and paired sample t-test. The results showed a significant increase in the ability to throw with a significance value of 0.001 (p < 0.05). Thus, UBPT exercises are effective in increasing the strength and explosiveness of the upper body muscles so that they can improve  the ability to throw into  football players.